Penggunaan Media Instagram Kopi Janji Jiwa Samarinda dalam Meningkatkan Customer Engagement - Setya, Andra Prianata; Boer, Kheyene Molekandella (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Kopi Janji Jiwa Samarinda is a coffee company that currently uses the Instagram application as a medium to promote its sales and also a tool to establish relationships with customers. One of the things that is still a problem is how it can maintain and increase its involvement between the use of Instagram media and customers of Janji Jiwa Samarinda coffee. The purpose of this study is to find out more about the use of Instagram media which is a form of promotion to sell products from Janji Jiwa Samarinda coffee and involve customers, because almost every business that promotes on Instagram certainly needs to involve customers. The method used in this research is descriptive qualitative method, data collection techniques conducted by researchers are through interviews, observation, and documentation. The primary data sources of this research are Kevin Candra Liandry as a content creator and Irfan Fadilah as the Main Manager as well as supporting sources from Dina's customers, and for secondary data in the form of documents from Kopi Janji Jiwa Samarinda. Based on the results of the research, the use of Instagram media has an influence in increasing customer engagement with the help of the theory of Strauss & Frost which states that there are 3 important pillars, namely: content engagement, media engagement, engagement marketing activities, as well as the 4C Theory by Chris Heuer which also supports this analysis with four main elements: context, communication, collaboration, connection. According to the results of the research, the three pillars can be manifested well, as in the first pillar shows the use of Instagram features utilizing comments, stories, and instant messaging features and the use of language that is easy to understand. Then the second pillar utilizes the most effective media, namely Instagram as the main media in involving its customers. The last pillar is well utilized such as providing promos, inviting customers to play quizzes, give away, mini games and also being consistent in uploading photos, videos, and stories. Through all these pillars and elements, Janji Jiwa Samarinda coffee has succeeded in maximizing customer engagement and maintaining their loyalty through interesting and consistent content on Instagram social media.